2022
DOI: 10.1021/acs.jpclett.2c00974
|View full text |Cite
|
Sign up to set email alerts
|

Suppression and Enhancement of Thermal Chemical Rates in a Cavity

Abstract: The observed modification of thermal chemical rates in Fabry−Perot cavities remains a poorly understood effect theoretically. Recent breakthroughs explain some of the observations through the Grote−Hynes theory, where the cavity introduces friction with the reaction coordinate, thus reducing the transmission coefficient and the rate. The regime of rate enhancement, the observed sharp resonances at varying cavity frequencies, and the survival of these effects in the collective regime remain mostly unexplained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
92
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 49 publications
9
92
3
Order By: Relevance
“…After completing this work, we noticed that two similar results were reported in the literature. [35,36] Our work is in agreement with these findings and differentiates itself from those works as we investigated the effect of imperfect cavities, both numerically and analytically, on chemical reaction rates while the other reports focused on perfect cavities.…”
Section: Discussionsupporting
confidence: 87%
“…After completing this work, we noticed that two similar results were reported in the literature. [35,36] Our work is in agreement with these findings and differentiates itself from those works as we investigated the effect of imperfect cavities, both numerically and analytically, on chemical reaction rates while the other reports focused on perfect cavities.…”
Section: Discussionsupporting
confidence: 87%
“…When nuclear quantum effects are negligible, QTST provides the same result as the GH theory. Further, both the GH theory and QTST predict only a mild suppression of chemical kinetics and a broad rate profile , as a function of photon frequency, in contrast to the much larger and sharper rate profile typically observed in experiments. ,, On the other hand, computational studies , at the single-molecule level revealed the enhancement of the chemical kinetics, especially when the molecule–bath coupling is weak…”
mentioning
confidence: 89%
“…Further, both the GH theory and QTST predict only a mild suppression of chemical kinetics and a broad rate profile 12,17 as a function of photon frequency, in contrast to the much larger and sharper rate profile typically observed in experiments. 1,5,8 On the other hand, computational studies 20,25 at the single-molecule level revealed the enhancement of the chemical kinetics, 25 especially when the molecule−bath coupling is weak. 28 Note that all such reaction theories are either classical or semiclassical in nature and do not address collective effects in a direct manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it illustrates clearly that the cavity influence on chemical reactivity can persist even at a large N ensemble and that the catalyzing and inhibiting effect could be present for the same chemical reaction. Recent work , showed promising progress, and yet much remains to be investigated. A conclusive understanding will likely demand a collaborative effort involving experimental work, ab initio theory, and simplified models.…”
mentioning
confidence: 99%